KOMUNIKASI PEMASARAN PARIWISATA: STUDI KASUS DINAS KABUPATEN PANGANDARAN - Dahliah, Dedeh (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
This study analyzes the tourism marketing communication strategies implemented by the Tourism and Culture Office of Pangandaran Regency to boost tourist visits. Using a qualitative case study approach, the research explores public relations activities, advertising, digital media utilization, event management, and collaboration with local partners. Findings reveal that integrated communication strategies, such as digital-based promotion through social media and official websites, as well as destination branding enhancement through tourism events and clear market segmentation, have successfully increased tourist visits. However, challenges such as limited promotional budgets, insufficient facilities, and the unadaptable mindsets of tourism actors hinder effectiveness. This study highlights the importance of marketing innovation, stakeholder collaboration, and digital technology optimization to strengthen Pangandaran's position as a leading tourism destination at the national and international levels.